Iron-rich slag addition in ternary binders of Portland cement, aluminate cement and calcium sulfate. (March 2022) - Astoveza, Jennifer; Trauchessec, Romain; Migot-Choux, Sylvie; Soth, Ratana; Pontikes, Yiannis
Abstract: The growing demand for sustainability in the recent decades has driven the exploration for new supplementary cementitious materials (SCM) such as the non-ferrous metallurgy (NFM) slags. In this study, the hydration of an iron-rich NFM slag incorporated in CAC-PC‑calcium sulfate ternary binders was investigated. The dimensional stability of mortars demonstrated the contribution of the slag addition in mitigating excessive expansion while maintaining an acceptable mechanical strength over 180 days. The degree of slag hydration estimated with X-ray Computed Tomography (XCT) support the activating effect of the PC, while isothermal calorimetry, XRD, TGA and ATR-FTIR were used to delineate the evolution of the phase assemblage. Finally, TEM-EDS revealed the incorporation of Fe in hydrate gels grouped into two clusters according to a Ca-Al-Si ternary diagram: (1) Al-rich gels in the formulation with no PC; and (2) intermixed hydrate gels associated with Ca, Al and Si in the formulations with PC. Highlights: High compressive strengths (40–50 MPa) obtained after 28 days despite lower proportion of cement in the dry mix The incorporation of the slag could improve the dimensional stability of expansive binders. The addition of PC in the ternary binder of CAC, HH and slag favors slag reactivity. The Fe from the slag is incorporated in intermixed hydrate gel phase.